A sphere theorem for a class of Reinhardt domains with constant Levi curvature - Hounie, Jorge; Lanconelli, Ermanno (Forum mathematicum, 2008)
We prove that a bounded Reinhardt domain of ℂ n+1 with C 2 boundary of constant Levi curvature with rotational symmetry in two complementary sets of variables is a ball. 2000 Mathematics Subject Classification: 53A07, 53O42; 35J70, 35B50, 32T99.